A pharmacogenetics study on acute pain perception among patents on methadone maintenance therapy (MMT) - Zahari, Zalina (2016)
OPRM1 and ABCB1 are involved in pain modulation and analgesic responses. It is possible that OPRM1 and ABCB1 polymorphisms contribute to inter-individual differences in experimental pain responses. The objectives of this study were to investigate the pharmacogenetic factors that influence pain responses in patients on methadone maintenance therapy (MMT) and opioid-naive individuals. The protocol for the study was approved by the Human Research Ethics Committee (HREC), USM in Kelantan, and the Medical Research & Ethics Committee (MREC), at the MOH, Malaysia. This cross-sectional study involved Malay males opioid-dependent patients receiving MMT from MMT clinics in Kelantan (n = 148) and healthy opioid-naive individuals from the local population (n = 152), recruited from March to October, 2013. Excluded were individuals with a positive result of urine screening for drug test, chronic or ongoing acute pain, and other conditions that may affect pain or cold pressor test (CPT). Written informed consent was obtained from the subjects after full explanation of the study procedure. Cold pain responses including pain threshold, pain tolerance, and pain intensity were measured using the CPT. DNA was extracted from whole blood and genotyped for OPRM1 and ABCB1 polymorphisms. This study revealed hyperalgesia among opioid-dependent patients, as manifested by their quicker detection of pain and quicker hand withdrawal. In healthy opioid-naive individuals, the 2677G>T/A polymorphism of ABCB1 was associated with pain threshold and pain tolerance. Inaddition, carriers of 3435T allele (3435 CT and TT genotypes) exhibited significantly higher pain intensity scores than carriers of the 3435 CC genotype. The 1236 CC/2677 GG/ 3435 CC diplotype was associated with a higher cold pain threshold and also pain tolerance. Individuals with 1236 TT/2677 TT/ 3435 TT diplotype exhibited higher pain intensity scores compared to those without this diplotype. However, OPRM1 polymorphisms were not associated with cold pain responses in opioid-naive individuals. In the opioid-dependent patients, the IVS2+691 CC genotype was associated with a lower pain tolerance, but AC/AG diplotype of 118A>G and IVS2+691G>C polymorphisms of OPRM1 were associated with a higher pain tolerance. The 2677G allele for 2677G>T/A polymorphism was associated with lower pain threshold and pain tolerance, and 2677G allele or CGC haplotype for the 1236C>T, 2677G>T/A, and 3435C>T polymorphisms of ABCB1 were associated with a higher pain intensity scores. The CGC/TTT diplotypes was associated with a higher serum methadone concentration. These findings may become the foundation for understanding of genetic contributions to experimental pain responses in opioid-dependent patients on MMT and opioid-naive individuals. ABCB1 polymorphisms may be a predictor for the treatment outcomes of opioid-dependent patients on MMT.